A generic transient PV system model for power quality studies. (April 2016) - Patsalides, Minas; Efthymiou, Venizelos; Stavrou, Andreas; Georghiou, George E.
Abstract: Currently, the deployment of PV technology in local distribution grids is usually done in an unplanned way without performing the required studies and this may induce power quality issues as penetration increases. The utilisation of accurate simulation models is therefore of great importance in an attempt to assess the real consequences of localised PV production. A generic PV system model for transient studies, the parameters of which can be tuned using transient data is proposed. The model is tuned and validated using transient data obtained from a detailed PV system circuit topology. The main novelty of this work lies in the fact that the proposed model can be tuned in order to represent accurately the dynamic behaviour of PV systems for both balanced and unbalanced conditions. Harmonics are also incorporated into the model to highlight its capability for use in complete power quality studies. The developed model is used along with the detailed PV system model to assess the voltage transient response of a distribution grid busbar. Finally, the transient behaviour of the distribution grid busbar having different grid impedance values is also evaluated utilising the proposed model. The expected and observed results are compared by means of the Theil Inequality coefficient depicting good agreement. Highlights: A generic PV system model is developed for transient studies. The model can be used to represent accurately the dynamic behaviour of PV systems. The new model is capable of simulating normal and unbalanced operating conditions. The transient response of voltage depends on the transient behaviour of PV systems.